THE VALUE OF ISLAMIC EDUCATION IN THE REIGN OF SULTAN OF STUDENT CHARACTER IN THE MODERN ERA MAHMUD MALIK AZ-ZAHIR: RELEVANCE FOR THE FORMATION : Nilai Pendidikan Islam dalam Pemerintahan Sultan Mahmud Malik Az-Zahir: Relevansi bagi Pembentukan Karakter Mahasiswa di Era Modern - Hawa Purnama Wati Hawa; Khonsa Latifa Nurrahmah; Afifah Zhafirah; Kamalsyah Panca Romadhoni; Rio Kurniawan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the values of Islamic education during the reign of Sultan Mahmud Malik Az-Zahir in the Samudera Pasai Sultanate and examine their relevance to the formation of student character in the modern era. The research focuses on the value of ḥubb al-ʿilm (love of knowledge) as a central principle underlying Islamic leadership, education, and moral development. This study employs a qualitative research design using a literature review approach. Data were collected from historical sources, classical and contemporary books, national and international journal articles, and relevant academic documents. The collected data were analyzed thematically to identify key educational values and their implications for higher education today. He findings indicate that Sultan Mahmud Malik Az-Zahir played a significant role in promoting Islamic education by supporting halaqah (learning circles), honoring scholars, and strengthening educational institutions as centers of knowledge and moral guidance. These efforts positioned Samudera Pasai as one of the earliest Islamic intellectual centers in Southeast Asia. The study also finds that the educational values practiced during his reign remain relevant for addressing contemporary challenges faced by university students, particularly moral decline and ethical issues in the digital era. The scientific contribution of this study lies in reinterpreting historical Islamic educational values as a conceptual foundation for character education in modern higher education, emphasizing the integration of intellectual excellence, moral integrity, and social responsibility.